Very Early Rehabilitation After Treatment with Intravenous Thrombolysis for Mild Acute Ischemic Stroke - Rahul R. Karamchandani; Liang Wang; Dale Strong; Alexis A. Mulvaney; Jonathan D. Clemente; Jeremy B. Rhoten (Neurology International)
Background/Objectives: The optimal timing of rehabilitation after acute ischemic stroke is unclear. We studied neurological outcomes and safety of early mobilization (EM) within 24 h for patients receiving intravenous thrombolysis. Methods: This was a retrospective analysis of patients treated at a single Comprehensive Stroke Center from 6/2020–10/2024 with EM versus usual care. Patients were eligible for EM if they were treated with intravenous thrombolysis and had post-treatment National Institutes of Health Stroke Scale scores ≤ 5, and later, ≤10. Ordinal regression was performed to determine factors associated with a 90-day functional outcome benefit in the full cohort. Propensity scores were calculated for matched sample pairs to determine any shift towards better outcomes with EM. Results: Groups of 165 and 73 patients were treated with EM and usual care, respectively. Treatment with EM was not associated with improved 90-day neurological outcome (odds ratio [OR] for higher mRS 0.746, p = 0.265). The groups also had comparable rates of symptomatic intracranial hemorrhage, length of stay, and discharge disposition. In the propensity score analysis of 73 matched pairs, EM was comparable to usual care with respect to 90-day functional outcome (OR for higher mRS 0.891, p = 0.7). Conclusions: Mobilization within 24 h resulted in comparable rates of 90-day neurological function, symptomatic intracranial hemorrhage, and hospital length of stay in patients with mild ischemic stroke treated with intravenous thrombolysis. Future trials may further investigate the safety and efficacy of EM in alternate and larger patient cohorts.